2017
DOI: 10.1159/000474958
|View full text |Cite
|
Sign up to set email alerts
|

Resting Heart Rate and Ischemic Stroke in Patients with Heart Failure

Abstract: Background: Although high resting heart rate (RHR) is known to be associated with an increased risk of mortality and hospital admission in patients with heart failure, the relationship between RHR and ischemic stroke remains unclear. This study is aimed at investigating the relationship between RHR and ischemic stroke in patients with heart failure in sinus rhythm. Methods: We examined 2,060 patients with systolic heart failure in sinus rhythm from the Warfarin versus Aspirin in Reduced Cardiac Ejection Fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In agreement with previous evidence [ 39 ], our data show that peak velocities are stable over time, but we showed for the first time that a reduction in HR is associated with increased LA stasis in SR. If confirmed in larger cohorts, this finding could provide novel insight into the finding that ivabradine (a negatively chronotropic agent) has been associated with an increased risk of incident AF [ 40 ] and ischemic stroke in patients with systolic heart failure in SR, in contrast to its beneficial effect on mortality and hospital re-admissions [ 41 ]. Nevertheless, HR changes are likely to only partially explain the temporal variability observed in LA stasis, given the mild correlation observed, and other factors are likely to also be involved.…”
Section: Discussionmentioning
confidence: 94%
“…In agreement with previous evidence [ 39 ], our data show that peak velocities are stable over time, but we showed for the first time that a reduction in HR is associated with increased LA stasis in SR. If confirmed in larger cohorts, this finding could provide novel insight into the finding that ivabradine (a negatively chronotropic agent) has been associated with an increased risk of incident AF [ 40 ] and ischemic stroke in patients with systolic heart failure in SR, in contrast to its beneficial effect on mortality and hospital re-admissions [ 41 ]. Nevertheless, HR changes are likely to only partially explain the temporal variability observed in LA stasis, given the mild correlation observed, and other factors are likely to also be involved.…”
Section: Discussionmentioning
confidence: 94%
“…On the same track, considering patients with heart failure with reduced left ventricular ejection fraction (HFrEF) in sinus rhythm who are treated with the current recommended medical regimen, which includes beta-blockers, Nakanishi et al [ 74 ], suggested a higher risk of ischemic stroke in those patients when they show low RHR. A high RHR is associated with increased mortality and hospital re-admissions in patients with HFrEF who are in sinus rhythm, and beta-blockers significantly improve the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was also observed in the adjusted analysis for the total AIS-HF population and the 65-74 age category of AIS-HF patients. Lower heart rates are associated with reduced hospitalizations and decreased mortality among HF patients [19,20]. Among older patients, optimal heart rate is reported to be between 70-76, and for every 10-point increase in heart rate, the risk of poor outcomes increases by 10% [19,21].…”
Section: Discussionmentioning
confidence: 99%
“…Lower heart rates are associated with reduced hospitalizations and decreased mortality among HF patients [19,20]. Among older patients, optimal heart rate is reported to be between 70-76, and for every 10-point increase in heart rate, the risk of poor outcomes increases by 10% [19,21]. This increase is reported to be independent of β-blocker use [22] and associated with a decrease in cardiac perfusion to myocardium exacerbating dysfunction [23].…”
Section: Discussionmentioning
confidence: 99%